Surgical Management of Hirschsprung's Disease: A Comparative Study Between Conventional Laparoscopic Surgery, Transumbilical Single-Site Laparoscopic Surgery, and Robotic Surgery - Li, Wei; Lin, Minghui; Hu, Hai; Sun, Quanfeng; Su, Cheng; Wang, Congjun; Li, Yanqiang; Li, Yong; Chen, Jiabo; Luo, Yige (Frontiers in Surgery, 2022)
Background Hirschsprung's disease (HD) is a commonly digestive malformation in children that usually requires surgery. This study aims to evaluate the short-term efficacy of conventional laparoscopic surgery (CLS), transumbilical single-hole laparoscopic surgery (TU-LESS), and robotic surgery (RS) in the treatment of Hirschsprung's disease. Methods 90 patients with Hirschsprung's disease undergone laparoscopic surgery at our center between 2015 and 2019, divided into three groups (group CLS, TU-LESS and RS), were retrospectively analysed. Results CLS and TU-LESS group showed no significant difference in operation duration (P > 0.05) but shorter operation duration than the RS group (P < 0.05). RS group had highest overall SCAR scores, while TU-LESS group had the lowest one (P < 0.05). Other parameters such as operative blood loss, hospital stays, recovery time of digestive function, postoperative complications had no significant difference among the three groups (P > 0.05). Conclusion The three surgical methods for HD revealed similar efficacy, where TU-LESS and CLS spent less time than RS; TU-LESS led to the most aesthetic effect, followed by CLS and RS.